Synthesis of flower-like monoclinic BiVO4/surface rough TiO2 ceramic fiber with heterostructures and its photocatalytic property. Issue 1 (January 2016) - Bao, Nan; Yin, Ze; Zhang, Qingzhe; He, Sui; Hu, Xinde; Miao, Xinhan
Abstract: The BiVO4 /surface rough TiO2 ceramic fibers were fabricated via a mild hydrothermal method by using surface-modified Si–TiO2 as self-supporting substrate materials. The as-prepared fibers consisted of the needle-like or flower-like BiVO4 uniformly assembled on surface rough TiO2 ceramic fibers (RTF). Notably, several needle-like BiVO4 with lengths less than 1 µm and diameters ranging from 80 to 100 nm constructed a microflower by radiating from the center, which could be controlled by adjusting the concentration of the precursor. The incorporation of monoclinic BiVO4 in the composites was confirmed by XRD, SEM, PL and XPS. RTF was obtained through the dissolution of silicon in the surface of Si–TiO2 ceramic fibers (STF) by HF. The photocatalytic performance of the heterostructured fibers was investigated by the degradation of X-3B in aqueous solution under both ultraviolet and visible light irradiation. The 0.2BiVO4 /RTF with mass ratio of 20% vanadate exhibited optimized photocatalytic activity compared with pure STF, BiVO4, 0.2BiVO4 /STF and mechanically mixed 0.2BiVO4 +RTF, which might be ascribed to synergistic effect of morphology and heterostructures. Moreover, such 0.2BiVO4 /RTF composites were easy to separate from the treated wastewater and remained stable after 10 irradiation cycles. It was proposed that electronic interactions at the interface of BiVO4 /RTF heterostructures could effectively inhibit the charge recombination.